"Improvement of concrete resistance f'c= 210 kg/cm2 adding steel chips and fiberglass, Cajamarca 2022" (LACCEI, 2024)
The present research work seeks to analyze and verify the resistance of concrete f'c = 210 kg/cm2 adding additives such as steel shavings and fiberglass, by carrying out tests in the concrete laboratory at the Universidad Privada del Norte - Cajamarca headquarters. The investigation is framed in an experimental way, considering as a hypothesis, to show that the addition of steel shavings and fiberglass to concrete f'c= 210 kg/cm2 is viable and profitable for construction, since these additives are accessible and economical. In the Peruvian market, all this was verified by comparing the compression tests at 7, 14 and 28 days, to corroborate the resistance of the concrete specimens carried out in the laboratory. Comparing the three types of concrete, the test tube that reached the highest resistance to compression and fracture was the concrete incorporated with fiberglass, obtaining f'c= 262.46 kg/cm2, being higher than that of the standard concrete and that of the concrete incorporating steel chip, with resistances of f'c= 234.61 kg/cm2 and f'c= 257.43 kg/cm2, respectively.